Investigating thermal mixing and reverse flow characteristics in a T-junction using CFD methodology. (5th June 2016) - Lin, C.H.; Ferng, Y.M.
Highlights: CFD simulates the thermal mixing and reverse in a T-junction. Steady-state turbulence models are adopted in this paper. Reverse flow in the T-junction decreases with increasing flowrate in main pipe. v2f turbulence model can capture the reverse flow from the branch injection. RKE model can reproduce the thermal mixing characteristics in a T-junction. Abstract: A three-dimensional (3-D) computational fluid dynamics (CFD) methodology is developed to simulate the thermal mixing and reverse flow characteristics in an in-house T-junction. Different steady-state turbulence models are adopted in the simulations and assessed against the measured data of temperature distributions at various cross-sections of the main pipe. The unsteady-state turbulence models may be suitable for resolving the amplitude and frequency of temperature oscillation in a T-junction. However, T-junctions are just one component in an entire complex piping system. The steady-state turbulence models therefore attract some interest for T-junction simulations in engineering applications. Two cases, with the flowrate combinations of 30/200 and 30/400 in the branch/main pipes, are used to validate CFD simulations with different turbulence models. The reverse flow from the branch back upstream of the T-junction intersection is more significant for the lower flowrate of the main pipe, which can be confirmed by both measured data and predicted results. Based on the temperature comparison of the measurements and the predictions, the v2f turbulence model is most suitable for capturing the flow reversal characteristics in the T-junction, while the realizable k – ε turbulence model reproduces the measured data more accurately for the T-junction with the higher flowrate in the main pipe and the lesser reverse flow. The present results can provide a useful reference for simulating the thermal mixing and reverse flow in a T-junction with various steady-state turbulence models.